Public sector decentralization and school performance: International evidence - Torberg Falch; Justina A. V. Fischer (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2010)
Using a panel of international student test scores 1980 2000 (PISA and TIMSS), panel fixed effects estimates suggest that government spending decentralization is conducive to student performance. The effect does not appear to be mediated through levels of educational spending.
Keywords: C33; H2; I2; H40; 330; Fiscal Decentralization; Student Achievement; Federalism; PISA; TIMSS; Education; School Quality